Biomass densification for minimal drying energy and optimised pellet quality - Lau, Johnson Ho Kwong (2025)
Biomass power generation has been gaining increasing importance globally in recent years to provide renewable energy and combat climate change. However, several constraints have limited the expansion of biomass power generation, and in particular, the use of alternative biomass feedstocks to wood. The major challenges of the industry include the high drying energy of biomass, the need for biomass densification and the variability in the properties of biomass. This thesis addresses several of the major challenges of the industry through the study of the properties of alternative biomass feedstocks, the development of a new novel low-energy biomass drying process, the in-depth investigation of biomass pelleting and pellet milling behaviour, and the use of Life Cycle Analysis (LCA) to study the environmental benefits of biomass power generation from a system perspective.